Improving Students' Spiritual Maturity Based on the Wisdom of Ahmed Yassavi (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Ahmed Yassavi's work "Devoni Hikmat" is important in literary studies as a unique example of Sufism literature. Yassavi sets the main goal of education and a number of tasks related to it in order to educate and raise a person to a perfect state. Ahmad Yassavi expressed his views to the masses through the work "Devoni Hikmat". The work "Devoni Hikmat" is a rare example of literature not only of the Turkic peoples, but also of the world. Ahmed Yassavi is a representative of religious and mystical literature.